Duplication of 8p23.1: a cytogenetic anomaly with no established clinical significance. Issue 6 (June 1998) - Barber, J C; Joyce, C A; Collinson, M N; Nicholson, J C; Willatt, L R; Dyson, H M; Bateman, M S; Green, A J; Yates, J R; Dennis, N R
Abstract : We present seven families with a cytogenetic duplication of the short arm of chromosome 8 at band 8p23.1. The duplication has been transmitted from parents to offspring in four of the seven families. In three families, the source of the extra material and its euchromatic origin were established using FISH with a YAC which was mapped to 8p23.1 and a whole chromosome paint for chromosome 8. FISH signals from this YAC were significantly larger on the duplicated chromosome compared with the normal chromosome in all six family members tested. Comparative genomic hybridisation (CGH) on a representative subject was consistent with these results. The families were ascertained for a variety of mostly incidental reasons including prenatal diagnosis for advanced maternal age. The transmission of this duplication by multiple phenotypically normal family members with no history of reproductive loss suggests the existence of a novel class of 8p23.1 duplications, which can be regarded as euchromatic variants or duplications with no phenotypic effect.